1989
DOI: 10.1002/hep.1840090412
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 repletion in cirrhosis with oral pyridoxine: Failure to improve amino acid metabolism

Abstract: This study evaluated the effect of daily oral pyridoxine supplementation in patients with cirrhosis. Eight subjects were treated with 25 mg of pyridoxine for 28 days. Before and after the supplementation period, B6 status was assessed by measuring fasting plasma vitamer levels and response to a 25 mg oral pyridoxine load. In addition, a 24-hr urine collection was analyzed during each load study for B6 metabolites. The data indicated that supplementation achieved repletion of peripheral B6 stores, as evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Unlike many causes of refractory seizures, vitamin B 6 deficiency is relatively simple to treat. Henderson et al demonstrated that supplementation with only 25 mg of oral pyridoxine daily for 28 days in patients with cirrhosis effectively replenished peripheral vitamin B 6 stores 23 . In the current report, all patients received 200 mg per day, which is double the daily dose of pyridoxine (100 mg/day) for adults recommended by the Food and Nutrition Board of the Institute of Medicine 29 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Unlike many causes of refractory seizures, vitamin B 6 deficiency is relatively simple to treat. Henderson et al demonstrated that supplementation with only 25 mg of oral pyridoxine daily for 28 days in patients with cirrhosis effectively replenished peripheral vitamin B 6 stores 23 . In the current report, all patients received 200 mg per day, which is double the daily dose of pyridoxine (100 mg/day) for adults recommended by the Food and Nutrition Board of the Institute of Medicine 29 .…”
Section: Discussionmentioning
confidence: 70%
“…Because none of our patients was receiving isoniazid or had a history of childhood seizures, it was assumed that dietary deficiency of vitamin B 6 was likely causative. This deficiency is unusual in adults because vitamin B 6 is so widely distributed in food, but deficiency has been associated with alcoholism and cirhossis 23 . ‐ 28 Vitamin B 6 deficiency is classically associated with peripheral neuropathy and anemia, and often other vitamin B‐complex deficiencies occur in patients with alcoholic liver disease 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient dietary intakes may cause vitamin B6 deficiency which subsequently induces seizures. Gerlach and colleagues (6) reported three cases of refractory seizures consequent to vitamin B6 deficiency which may be aggravated by alcoholism or liver disease (31)(32)(33)(34)(35). Low PLP concentration in those patients may occur over time owing to a dietary deficiency coupled with intact aldehyde oxidase activity.…”
Section: Dietary Deficiency Of Vitamin B6mentioning
confidence: 99%
“…Although a single dose of vitamin B-6 supplementation (50 mg/d) did not show a significant effect on the GSH and GSSG levels and activities of GSH-Px, GSH-Rd, and GSH-St in patients with hepatocellular carcinoma [14], the combination of vitamin B-6 and GSH supplementation are likely to have antioxidative effects in liver cirrhosis patients. Since an impaired vitamin B-6 and GSH status has been observed in patients with liver cirrhosis [15][16][17][18][19], a strategy is required to either maintain adequate or increase vitamin B-6 and GSH status in order to cope with the altered oxidative stress and antioxidant capacities in this specific group of patient. However, it remains unclear whether supplementation with vitamin B-6 or GSH could compensate for their reduced status, and improve the antioxidant capacity of liver cirrhosis patients.…”
Section: Introductionmentioning
confidence: 99%